Morphology of the complete larval stages of Portunus segnis (Forskål, 1775) (Crustacea: Brachyura: Portunidae) from the Gulf of Aqaba, Saudi Arabia - Al-Aidaroos, Ali M.; Kumar, A. A. J.; Al-Haj, Ahmed E.; Al-Sofyani, Abdulmohsin; Crosby, Michael P.; El-Sherbiny, Mohsen M. (Zootaxa, 2019)
Portunus pelagicus (Linnaeus, 1758) sensu lato has been recognized as a species complex comprising four species. Of these four species, the larval stages of all except Portunus segnis (Forskål, 1775), have been described. The larvae of P. segnis, hatched from an ovigerous female, caught in the Gulf of Aqaba, were cultured in the laboratory up to the megalopa stage. All the larval stages are described herein for the first time. The number of aesthetascs of the antennules of all the zoeal stages of P. segnis differs from those of the larvae of the other species of the P. pelagicus species complex. In the telson forks of zoea I–IV of P. segnis, there is a pair of ventral spines and two pairs of dorsal spines, whereas in the other P. pelagicus species complex larvae, there is a pair each of ventral and dorsal spines. Another unique feature, in the megalopa of P. segnis, are two endopod hooks in pleonites I–V. Different zoeal and megalopal stages of P. segnis can be distinguished clearly from the other P. pelagicus species complex larvae based on the number of setae and patterns of different appendages.